2009
DOI: 10.1111/j.1600-0404.1975.tb02824.x
|View full text |Cite
|
Sign up to set email alerts
|

EXPERIMENTAL BRAIN DAMAGE FROM FLUID PRESSURES DUE TO IMPACT ACCELERATION. 1. Design of Experimental Procedure

Abstract: The significance of the intracranial acceleration prcssure pattern at impact to the intact skull in production of brain damage is discussed particularly as regards the contre-coup pressures. Sudden pressure changes within the cranial cavity of the rabbit were studied by means of a new impact acceleration model. The rabbit skull was connected with a cylinder. Impact acceleration was applied to the model with the skull contents serving as a "contre-coup end". Skull deformation was minimized by reinforcement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Suh et al (1972) found that when impacting a fluid-filled spherical shell, negative pressure regions were not located at the contrecoup site. Other researchers found that negative pressure did not contribute to injury when impacting animal models such as rabbits and Macaques (Stalhammar, 1975a, 1975b; Stalhammar and Olsson, 1975; Nuscholtz et al, 1984). Nuscholtz et al (1984) concluded from their research that cavitation was not a mechanism of injury for contusion, but that head and neck position during impact was of greater importance.…”
Section: Intracranial Pressure Gradients Produced From Impactmentioning
confidence: 95%
“…Suh et al (1972) found that when impacting a fluid-filled spherical shell, negative pressure regions were not located at the contrecoup site. Other researchers found that negative pressure did not contribute to injury when impacting animal models such as rabbits and Macaques (Stalhammar, 1975a, 1975b; Stalhammar and Olsson, 1975; Nuscholtz et al, 1984). Nuscholtz et al (1984) concluded from their research that cavitation was not a mechanism of injury for contusion, but that head and neck position during impact was of greater importance.…”
Section: Intracranial Pressure Gradients Produced From Impactmentioning
confidence: 95%
“…29 A simple model of the hydrostatic gradients generated within the brain can provide a rudimentary approximation of these pressures and can also predict the effect of pressure-relieving openings (eg, foramen magnum) on the resulting pressure gradients. 30 Experimental measures of the human surrogate response to impact loading also provide key insight into how local impact from a blunt impactor causes a subsequent acceleration of the head and pressure gradient within the cranial contents. Based on these data, the ability to predict, a priori, the pressures generated within the brain under a known external loading condition has improved substantially with the advancement of computationally based finite element models in the past two decades (for recent publications, see Refs.…”
Section: Mechanisms Of Damage—how Does the Mechanical Energy Of Motiomentioning
confidence: 99%
“…This problem can be solved by attaching a long column of fluid to a craniotomy and striking the top of the column. This approach created negative pressures and functional deficits in a rabbit model (Stålhammar 1975b , 1975a ; Stålhammar & Olsson 1975 ). Nusholtz et al detected negative pressures with a limiting value consistent with cavitation during head impacts in human cadavers and living primates.…”
Section: The Pathological Consequences Of Cavitationmentioning
confidence: 99%